Answer: undefined in both cases.
Explanation:
1) Expression to evaluate:
[tex] \frac{3}{2x^2} - \frac{2}{x^2-3x} [/tex]
2) You are asked to evaluate that expression for two different cases, x = 0 and x = 3.
3) First case: x = 0
The expression cannot be evaluated at x = 0, because the denominators (both denominators) equal 0, and the division by 0 is not defined.
So, the answer is undefined.
4) Second case, x = 3
When you replace x = 3 you get:
[tex] \frac{3}{2x^2} - \frac{2}{x^2-3x} = \frac{3}{2(3^2)} - \frac{2}{3^2-3(3)} = \frac{3}{18} - \frac{2}{9-9} [/tex]
Again, this result in a division by 0, so you conclude that it is undefined too.